The Islamic Regular Charity between The Immediacy and The Lagging - المدرس المساعد عثمان رحیم محمد الجبوري (College of Education for Women, 2019)
The islamic legitimacy,imposition and of al-zakkat(regular charity) are well known matters to the whole muslims but being in love with the present life and worldly existence and being in scare of the death made some of the moslems to lag behind and delay of keeping with that matter (regular charity) because the mony al wayes was the reason for the man happiness in the present life allah makes al-zakat (regular charity) one of the granting remissionns of the moslems people sins in return for that allah promised the moslems to honored them with the eternal life in in the paradise where is the gardens beneath which rivers flow so that I decided to write in this matter of couarse after trust and recommend in god and her it is in the readers' possession and hands under the title of "Al-zakat Bain Al-Foar Wal TaraKhi" which is mean "the Islamic regular Charity between the immediacy and the lagging down (delaying)". I made research up of two field of discussion or research, and I abbreviated the research to be in an agreeable to the requirement of writing a research if it is God's will. The first field of this research was about the definition of the word "Al-Zakat". Also, it was about the legitimacy of the "regular Charity". The first requirement of the firs field of the research (which was about the idiomatic and linguistic definition of the word "Al-Zakat"), explains that this word refers linguistically to the increasing and growing up, and it refers idiomatically to the Charity of a part of any money which got grow up to it's quorum for the deservers. The second requirement was about the Islamic legitimacy and decision of the regular charity. It was clear from the verse of the holly Koran and the Hadith (Prophetic tradition), that the regular charity is legislated and obligated to do. The second field of this research which was about the postponement and delaying of the regular charity, a-as consisting of two requirements: The first one was about the obligation of the regular charity between the immediacy and the delaying. It was clear that the regular charity must hot be delayed except if there was an execution and it preferred to be immediacy. Allah desired to be immediate worship, because of the Moslems people necessity for funds. Also, there are many Islamic legitimate standards confirming this matter. The second requirement was the immediacy of the Islamic regular Charity before the time of its obligation. It was clear that the regular Charity would not be obligated without the completion of the man's regular quorum, and the completion of the man's year of age. Some it would be advanced or earlier than it's regular time not for any reason, bat for the emergency need for that, for being in a hurry for the worship of god, and for the quittance from the rights and obligations towards Allah. And that matter has many Islamic legitimate statements.